Peran Organisasi Santri dalam Mendisiplinkan Shalat Berjamaah Santriwati di Pondok Pesantren Modern Adlaniyah Kabupaten Pasaman Barat - Nurhaliza Fitri; Mustafa (ALSYS, 2026)
Although the role of student organizations in fostering discipline has been widely studied, research specifically examining the role of female student organizations in disciplining female students’ performance of congregational prayers in modern Islamic boarding schools remains limited. This study aimed to describe the role of the Organisasi Santri Pesantren Adlaniyah (OSPA) in disciplining female students’ congregational prayers and to identify its supporting and inhibiting factors. This study employed a qualitative approach with a descriptive method. Data were collected through observations, in-depth interviews, and documentation at Pondok Pesantren Modern Adlaniyah, Pasaman Barat Regency. The research informants consisted of the OSPA supervisor as the key informant, OSPA administrators as the primary informants, and female students as supporting informants, who were selected using purposive sampling. Data were analysed using the interactive model of Miles and Huberman, which comprises data reduction, data presentation, conclusion drawing, and verification, while data validity was examined through technique triangulation. The results showed that OSPA performed five interrelated roles in disciplining congregational prayers, namely as a supervisor, motivator, mentor, role model, and enforcer of regulations. Factors supporting the performance of these roles included the active involvement of OSPA administrators in carrying out their duties, the existence of Islamic boarding school rules and policies, and support and guidance from female religious teachers and the OSPA supervisor. Meanwhile, the inhibiting factors included suboptimal cooperation among OSPA administrators, limited supporting facilities, and the influence of an undisciplined environment and peers. This study confirms that student organizations play a strategic role in fostering religious discipline through structured supervision, habituation, role modelling, guidance, and rule enforcement. These findings extend the application of habituation theory and the concept of Islamic organization to the context of enforcing religious discipline through student organizations and provide practical implications for Islamic boarding school administrators in strengthening a systematic and sustainable disciplinary system. Future research may examine the role of male student organizations or the implementation of discipline in other forms of worship.